ChemInform Abstract: From Phosphine‐Promoted to Phosphine‐Catalyzed Reactions by in situ Phosphine Oxide Reduction. Issue 46 (27th October 2016) - Voituriez, Arnaud; Saleh, Nidal
Abstract: Review: 46 refs + subrefs.